Efficacy of oral prednisolone in active ankylosing spondylitis: results of a double-blind, randomised, placebo-controlled short-term trial. Issue 1 (26th April 2013) - Haibel, H; Fendler, C; Listing, J; Callhoff, J; Braun, J; Sieper, J
Abstract : Background: The efficacy of oral prednisolone in patients with active ankylosing spondylitis (AS) has not been studied to date. Methods: In this double-blind, randomised, placebo-controlled trial, patients with AS with active disease despite taking non-steroidal antirheumatic drugs were randomised to three groups in which they were either treated with 20 mg (n=13) or 50 mg (n=12) of prednisolone, or placebo (n=14), administered orally every day for a total of 2 weeks. The primary endpoint was defined as a 50% improvement of the Bath AS Disease Activity Index (BASDAI) at week 2. Results: The primary endpoint was reached in 33% and 27% of the patients treated with 50 and 20 mg of prednisolone, respectively, versus only 8% on placebo (p=0.16 and p=0.30). However, the mean improvement of BASDAI score was significantly higher in the 50 mg prednisolone compared to the placebo group (2.39±0.5 vs 0.66±0.49, p=0.03), while there was only a small change in the 20 mg group (1.19±0.53; p=0.41). The results for other outcome parameters were similar. Conclusions: Oral prednisolone 50 mg per day, but not low dose prednisolone, showed a short-term response that was significantly higher than placebo. The clinical significance and the duration of this effect warrant further study. ClinicalTrials.gov Identifier: NCT00244166